Perylene Tetracarboxylic Diimide: Characterization and Its Role in the Electrical Properties of an Ag/N-BuHHPDI/PEDOT:PSS/p-Si Heterojunction Device - Zeb, Muhammad; Tahir, Muhammad; Muhammad, Fida; Khan, Dil Nawaz; Sayyad, Muhammad Hassan; Said, Suhana Mohd; Wahab, Fazal (Springer, 2020)
This paper reports on the thin film characterization of a synthesized small molecular semiconductor N-butyl-N′-(6-hydroxyhexyl) perylene-3,4,9,10-tetracarboxylic acid diimide (N-BuHHPDI) and its potential use in Ag/N-BuHHPDI/PEDOT:PSS/p-Si heterojunction device. The device is fabricated using spin coating of a conducting polymer PEDOT:PSS on p-Si substrate followed by thermal deposition of a 100-nm-thin layer of N-BuHHPDI. To complete the fabrication of Ag/N-BuHHPDI/PEDOT:PSS/p-Si heterostructure, silver (Ag) is used as the top electrode. The device shows non-ohmic and asymmetrical current–voltage (I–V) characteristics in dark conditions at 25°C which confirm the successful formation of rectifying heterojunction. Various diode parameters such as ideality factor (n), barrier height (ϕb), series resistance (Rs) and charge carrier mobility across the interface of the heterojunction are measured from the I–V characteristics. The non-ideal behavior of the diode is correlated with the film morphology obtained by atomic force microscopy. Fourier transformed infrared spectroscopy is performed to confirm the successful preparation of N-BuHHPDI. The fluorescence lifetime (22 ns) of the N-BuHHPDI thin film is measured via fluorescence spectroscopy. Different charge conduction mechanisms including the dominant one are studied for the fabricated device. © 2019, The Minerals, Metals & Materials Society.